2014
DOI: 10.1002/pd.4326
|View full text |Cite
|
Sign up to set email alerts
|

Integration of noninvasive prenatal prediction of fetal blood group into clinical prenatal care

Abstract: Incompatibility of red blood cell blood group antigens between a pregnant woman and her fetus can cause maternal immunization and, consequently, hemolytic disease of the fetus and newborn. Noninvasive prenatal testing of cell-free fetal DNA can be used to assess the risk of hemolytic disease of the fetus and newborn to fetuses of immunized women. Prediction of the fetal RhD type has been very successful and is now integrated into clinical practice to assist in the management of the pregnancies of RhD immunized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 95 publications
0
23
0
1
Order By: Relevance
“…4 As the discovery of cell-free fetal DNA in maternal blood is over 15 years ago, 5 the analysis of cell-free fetal DNA has been implemented for specific clinical applications such as fetal sex-determination to support the prenatal diagnosis of X-linked disorders 6 and fetal RhD status. 7 Research on the use of non-invasive prenatal diagnosis (NIPD) for the diagnosis of single gene disorders has to implementation for some conditions 8 and there is considerable support by prospective parents and health professionals for further development in this area. 9,10 European guidelines on the provision of prenatal-testing stress the need for prenatal testing to be offered without coercion, and also that provision of accurate, understandable information be provided to ensure a fully informed choice.…”
Section: Introductionmentioning
confidence: 99%
“…4 As the discovery of cell-free fetal DNA in maternal blood is over 15 years ago, 5 the analysis of cell-free fetal DNA has been implemented for specific clinical applications such as fetal sex-determination to support the prenatal diagnosis of X-linked disorders 6 and fetal RhD status. 7 Research on the use of non-invasive prenatal diagnosis (NIPD) for the diagnosis of single gene disorders has to implementation for some conditions 8 and there is considerable support by prospective parents and health professionals for further development in this area. 9,10 European guidelines on the provision of prenatal-testing stress the need for prenatal testing to be offered without coercion, and also that provision of accurate, understandable information be provided to ensure a fully informed choice.…”
Section: Introductionmentioning
confidence: 99%
“…Terminated fetuses have been subject to trauma, and prolonged cell-culture often results in genetic changes (Sambuy et al 2005;Li et al 2007). Other fetal material used for diagnostic purposes includes cell-free DNA in the maternal blood, which has been applied clinically for fetal Rhesus D detection and gender determination since 2001 (Lewis et al 2012;Clausen 2014;Hyland et al 2014). More recently, cell-free fetal (cff ) DNA in maternal plasma has been used to screen for fetal aneuploidies (Song et al 2013;Bianchi et al 2014).…”
mentioning
confidence: 99%
“…A non-invasive fetal RHD genotyping service is now available in many countries, with some also offering NIPD for c, E, C and Kell sensitised women 12. NIPD for routine fetal RHD genotyping has recently been shown to be highly accurate and has potential for use in maternity care to direct the use of antenatal prophylaxis using anti-D immunoglobulin 13. In Denmark and The Netherlands, this service is currently offered between 25 weeks’ and 28 weeks’ gestation,13 but earlier RHD genotyping could maximise the benefits by further reducing the costs and risks of unnecessary anti-D (a human blood product) administration for earlier sensitising events as well.…”
Section: Using Cffdna In Clinical Practicementioning
confidence: 99%
“…NIPD for routine fetal RHD genotyping has recently been shown to be highly accurate and has potential for use in maternity care to direct the use of antenatal prophylaxis using anti-D immunoglobulin 13. In Denmark and The Netherlands, this service is currently offered between 25 weeks’ and 28 weeks’ gestation,13 but earlier RHD genotyping could maximise the benefits by further reducing the costs and risks of unnecessary anti-D (a human blood product) administration for earlier sensitising events as well. A recent UK study has shown that fetal RHD genotyping using a high throughput methodology is robust enough to be used routinely from 11 weeks’ gestation to direct subsequent anti-D prophylaxis,14 and women and health professionals alike would welcome the introduction in order to avoid unnecessary anti-D administration 15.…”
Section: Using Cffdna In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation